Peran Budaya Pembelajaran dan Knowledge Management: Terhadap Kinerja Perusahaan: Studi Kasus PT XYZ - Purnama, Mirawati; Budihardjo, Andreas (Universitas Prasetiya Mulya, 2008)
Nowadays, food industries face a lot of challenges and problems at the same time, as business competition is very tough. People’s compsumtion life style changes, and raw food material becomes scarce; therefore, PT XYZ, which is a family business company, has to struggle to survive and grow. In fact, innovation becomes one of the most important factors that leads companies to win the competition. PT XYZ, therefore, has to keep on innovating its production process and products. Being innovative means that PT XYZ has to apply learning culture as it encourages knowledge management (KM). In other words, the learning culture will support the KM activities, which eventually will result in high corporate performance. This article discusses to which extent PT XYZ has adopted learning culture reflected on the seven dimensions of Learning Organization. A quantitative analysis was used to identify current learning culture, and a qualitative approach was used to explain the role of knowledge management in the learning culture. In addition to it, activirties which are related to innovation, knowledge management and corporate performance are described.